2011 10th Annual Workshop on Network and Systems Support for Games 2011
DOI: 10.1109/netgames.2011.6080978
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual view inconsistency: An objective evaluation framework for online game quality of experience (QoE)

Abstract: The ultimate goal of both game developers and network engineers is to provide a satisfactory quality of experience (QoE) for players. Most past works resort the subjective approaches to assess QoE which have serious limitations. But because of the interdependency of the quality metrics on game playability and the involvement of many players' subjective factors, defining an objective evaluation methodology for QoE faces some challenges. This paper presents an objective evaluation framework for QoE which based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 11 publications
0
22
0
Order By: Relevance
“…In [28], the metric used to evaluate the prediction error takes temporal aspects into account in order to optimize the perceived inconsistency. Chen and Zarki [10] provide an objective evaluation framework for Quality of Experience (QoE) in Games. QoE takes not only the precision but three basic perceptions into account: responsiveness, precision, and fairness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In [28], the metric used to evaluate the prediction error takes temporal aspects into account in order to optimize the perceived inconsistency. Chen and Zarki [10] provide an objective evaluation framework for Quality of Experience (QoE) in Games. QoE takes not only the precision but three basic perceptions into account: responsiveness, precision, and fairness.…”
Section: Discussionmentioning
confidence: 99%
“…While we do not provide a user study of how better predictions improve the quality of game play for players, the effects of these prediction errors, as the inconsistencies perceived by players, have been well studied [8,10,27,28]. Therefore, AntReckoning can be used to both improve the network requirements of games as well as the quality of game play.…”
Section: Performance Evaluationmentioning
confidence: 99%
“…Measuring Quality of Experience (QoE) [21], quantitatively, has always been hard. However, factors that directly impact the user experience have been well documented, specifically in a well-studied game such as Quake III (and similar games) [9].…”
Section: Performance Characteristics and Comparisonmentioning
confidence: 99%
“…Several recent studies have been conducted in order to elaborate objective models to assess the quality of experience (QoE) in the context of online games. In [7], the authors have identified three key parameters to measure the QoE : responsiveness, precision and fairness. The responsiveness is related to the perception of the player to the overall game process.…”
Section: Introductionmentioning
confidence: 99%
“…It represents the difference between all players' gaming environments. Consistency has also been identified as a critical parameter for measuring QoE [7], [16]. The consistency of views reflects the coherence and synchronization of sequences observed by different players.…”
Section: Introductionmentioning
confidence: 99%